Sistem Informasi Pemesanan Makan Berbasis Mobile pada Warung Bunda Ranti - Alda, Muhamad; Apriani, Devi; Hsb, Ronny Ramadhan; Tama, Agung Aulia (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The development of technology at the present time is developing rapidly, it can also have a big impact on the world of culinary business, one of which is the Bunda Ranti stall. Warung Bunda Ranti also requires an information system to provide easy service, both for customers ordering food and sellers serving customers. The design of an information system for ordering management at the Bunda Ranti stall can provide solutions in solving the problems found at the Bunda Ranti shop to make it more effective and efficient, especially in online ordering service management. By using codular, this information system design was successfully implemented and facilitated online service management at the Bunda Ranti shop.